Social Inequality and Social Mobility: The Construed Diversity of Ethiopian Female Labor Migrants in Djibouti - Eresso, Meron Zeleke (African Human Mobility Review, 2021)
Discussions about female labor migrants from the Horn of Africa are often loaded with accounts describing them as a homogenized group of destitute people on the move. Such trends of homogenization often hide the diverse social classes within these groups and the differential access co-nationals have across such social classes. Moreover, such discourses conceal the differences in migrants’ migration trajectories and related variances in their overall integration processes. This paper accentuates the heterogeneity of the social classes of Ethiopian female migrants and argues that the term Ethiopian female migrant is a parasol that often obscures the diverse and highly stratified migrant group. By going beyond this dominant trend of homogenization, this study addresses how differential access to economic resources, different social characteristics of migrants, and migrants’ settlement patterns impact migrants’ networks and their status within the larger Ethiopian female migrant group.